2012
DOI: 10.7314/apjcp.2012.13.2.633
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of a Proliferation-inducing Ligand (PRIL) Suppresses the Proliferation of Gastric Cancer Cells

Abstract: Asian Pacific J Cancer Prev, 13, 633-636 IntroductionGastric cancer (GC), the second most common cause of cancer-related death in the world, can develop in any part of the stomach and spread throughout the stomach and to other organs. There are about 1,000,000 new diagnoses and 800,000 deaths worldwide each year (Kamangar et al., 2006). The 5-year survival rate for curative surgical resection ranges from 30-50% for patients with stage II disease and from 10-25% for patients with stage III disease. The operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Recently, silibinin has received more attention for its anticancer, chemopreventive efficacy and nontoxic roles in humans (Cheung et al, 2010;Deep et al, 2010;Li et al, 2010). Extensive vitro and vivo studies show that the anticancer role of silibinin by regulating cell proliferation, angiogenesis and metastasis in various cancers (Cui et al, 2012;Wang et al, 2013). A variety of signaling pathways associated with cell proliferation have been identified to be involved in the anticancer actions of silibinin (Singh et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, silibinin has received more attention for its anticancer, chemopreventive efficacy and nontoxic roles in humans (Cheung et al, 2010;Deep et al, 2010;Li et al, 2010). Extensive vitro and vivo studies show that the anticancer role of silibinin by regulating cell proliferation, angiogenesis and metastasis in various cancers (Cui et al, 2012;Wang et al, 2013). A variety of signaling pathways associated with cell proliferation have been identified to be involved in the anticancer actions of silibinin (Singh et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators suggested that TNFSF13 can induce cell proliferation and is overexpressed in some kinds of solid tumor tissues or cells, including head and neck squamous cell carcinoma [12][13][14][15]. In this study, we provide evidence that TNFSF13 can be used as a biomarker for diagnosis and prognosis in LSCC and plays a significant role in LSCC carcinogenesis.…”
Section: Discussionmentioning
confidence: 67%
“…As a result, an siRNA specific for APRIL mRNA was designed and transfected different GC cell line cultures. The researchers successfully demonstrated the inhibition of cell viability and colony formation due to cell cycle arrest in the G2/M phase (Cui et al, 2012). These findings provide new clues to the investigation of GC malignant proliferation using the APRIL gene as target.…”
Section: Introductionmentioning
confidence: 89%
“…The lentiviruses belong to the family of retroviruses and can be used to deliver RNAi (now called shRNA). This shRNA is transfected and integrates into the cell genome, and after gaining stability in prolonged shRNA expression, it keeps the gene silenced (Naldini et al, 1996;Fish and Kruithof, 2004), this being one of the exogenous genes delivery systems preferred by some of the researchers cited in this review (Cui et al, 2012;Liu et al, 2012;Zhou et al, 2012). Several strategies are theoretically proposed for targeting these molecules in order to ensure a better specificity in the target tissue, but tests are necessary which allow demonstrating efficacy in practice.…”
Section: Introductionmentioning
confidence: 99%